Impact of inventory management on the financial performance of the firm: Al-Nawasi General Trading and Contracting Co. - Hossain, Arif (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2015.